2011
DOI: 10.1007/s11739-011-0568-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of separate venipunctures for IV access and laboratory studies decreases hemolysis rates

Abstract: Emergency department (ED) patients routinely undergo placement of a saline lock device (SLD) with the aspiration of blood for laboratory testing. Drawing blood through a SLD may result in hemolysis of sample, repeated venipuncture and increased ED length of stay (LOS). The objective of this study was to examine if separate venipunctures for intravenous (IV) access and laboratory studies decrease the rate of hemolysis and ED LOS. The study was conducted at an urban university level 1 trauma center with an ED vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…there is no additional clinical rationale), then best practice would be to not insert a PIVC. In support of their case, blood aspiration through PIVCs is associated with increased haemolysis compared with direct venepuncture . Haemolysis accounts for 40–60% of blood specimen rejections, leading to inaccurate results and repeated draws that cause pain, delay treatment decisions and increase in length of stay .…”
Section: Introductionmentioning
confidence: 99%
“…there is no additional clinical rationale), then best practice would be to not insert a PIVC. In support of their case, blood aspiration through PIVCs is associated with increased haemolysis compared with direct venepuncture . Haemolysis accounts for 40–60% of blood specimen rejections, leading to inaccurate results and repeated draws that cause pain, delay treatment decisions and increase in length of stay .…”
Section: Introductionmentioning
confidence: 99%
“…The findings from our study of an independent association between device and hemolysis suggest that changing the method for drawing blood from IV catheter to butterfly needle can reduce the rate of hemolysis without requiring any other modifications to phlebotomy method. This inference is supported by results from an interventional study that compared the hemolysis rate before and after initiation of a policy requiring use of a butterfly needle to collect blood for laboratory analysis . The investigators found the rate of all hemolysis fell from 23% in a 1‐week observation period when blood was drawn via IV catheters to 6.6% in the 4 weeks after the change in policy.…”
Section: Discussionmentioning
confidence: 90%
“…Previous investigations of ED phlebotomy have sought to identify remediable factors associated with in vitro hemolysis, including the role of straight needles (variably referred to as straight needles, butterfly needles, or steel needles) versus intravenous (IV) catheters, the gauge of the IV catheter, use of vacuum tube collection system or syringe, extension sets, anatomic location of the phlebotomy, perceived difficulty of blood draw, specimen tube size, fullness of the tube, and the method of tube delivery to the laboratory . The strongest finding was that the rate of hemolysis is higher when blood is drawn through IV catheters than through straight needles.…”
mentioning
confidence: 99%
“…In our opinion, this kind of training program should instead be strongly recommended and performed worldwide. Moreover, previous investigations had shown that educational program and technological interventions for phlebotomists are relevant and promote decrease of sample errors consequently resulting in quality improvement (16–19). Maybe Bölenius et al .…”
Section: Discussionmentioning
confidence: 99%